I soffitti lignei di palazzo Stati Cenci Maccarani a Roma - Antonucci, Micaela (Opus Incertum, 2018)
The palace of Cristoforo Paolo Stati (1498-1550), built between the Pantheon and piazza Navona in the rione Sant’Eustachio, is one of the few architectures of Giulio Pippi, aslo known as Romano (1499?-1546) in Rome. The construction of the palace probably began before Giulio moved to Mantova in 1524, and after the marriage of Cristoforo Stati and Faustina Cenci in 1520. Despite its small size, the building has a noble and solemn appearance and rich interior decorations, comparable to those of prestigious palaces of Cardinals and Popes; in its “public” rooms the wooden ceilings and the frescoes attributable to Perino del Vaga’s studio, celebrate the nobility, richness and artistic culture of its owner. The essay focuses on the analysis of the 16th century core of the palace and in particular on the wooden coffered ceilings, whose original features can be reconstructed thanks to the newly explored records of the 20th century restorations in the archives of the Technical Service of the Senate of the Italian Republic.